Comparison of patient length of stay in care between homebased care and hospitalized covid-19 patients in northern and West Nile regions, Uganda - Namusoosa, Ritah; Tamale, Andrew; Baziira, Joel; Ssekyanzi, Micheal; Nabadda, Susan N.; Kungu, Joseph M (Research square, 2023)
SARS-CoV-2-caused COVID-19 was first detected in Wuhan, China, in December 2019. Uganda reported her first COVID-19 case on March 21, 2020. The pandemic placed an enormous burden on health systems across the world. This retrospective cross-sectional study compared COVID-19 patient length of stay in care and associated factors for hospitalised patients in Regional Referral Hospitals and those who underwent home-based care in Northern and West Nile regions in Uganda. 400 patients were studied (200 inpatients and 200 home-based). All patients were confirmed COVID-19 cases with a positive real-time PCR test result. Regardless of signs or symptoms development, all individuals with confirmed SARS-COV2 infection were eligible for admission to the hospital during this period. It was found that hospitalized and home-based care patients were similar. 61.1% died within 14 days and 59.9% recovered under both types of care. Hospitalized patients stayed 14.8 days and home-based patients 15.0. The difference in the mean length of stay in care among hospitalized patients and patients under home-based was not statistically significant (t=0.28, p=0.38) and there was no association between type of care and length of stay in care (OR: 0.96: 95% CI 0.64 to 1.43: p=0.837). Symptom Status of patients and their occupation were found to be one of the important factors influencing recovery. It was observed that symptomatic patients were associated with longer stay in care (OR: 1.96, p=0.01). Likewise, law enforcement officers had a higher likelihood of staying longer compared to people involved in health-related work (OR: 3.28, p=0.03). Covid-19 patient length of stay in care is not dependent on the approach used in case management. Therefore, the decision of whether a patient should be hospitalised or treated at home requires careful consideration of all relevant factors and an individual evaluation of the patient's circumstances.
Keywords: COVID-19; Hospitalisation; Home-based care; Uganda